Interplay Between Sialic Acids, Siglec-E, and Neu1 Regulates MyD88- and TRIF-Dependent Pathways for TLR4-Activation During Leishmania donovani Infection - Karmakar, Joyshree; Mandal, Chitra (Frontiers in Immunology, 2021)
TLR4 activates two distinct signalling pathways involving adaptors MyD88 and TRIF to produce proinflammatory cytokines and type-I interferon respectively. How Leishmania donovani suppresses these pathways in not well studied. We earlier reported, TLR4 is hypersialylated due to reduced membrane-bound neuraminidase (Neu1) on infected-macrophages. We hypothesised that such enhanced sialoglycoconjugates on host cells may modulate the interactions with siglecs- which are the inhibitory receptors. Here, we examined the impact of such sialylation on overall TLR4 activation. Supporting this hypothesis, we demonstrated siglec-E engages hypersialylated TLR4 during infection. Such sialic acids-siglec-E interaction enhanced siglec-E phosphorylation that mediated its strong association with SHP1/SHP2 and also upregulated their phosphorylation. Pre-treatment of parasites and host cells with neuraminidase reduced SHP1/SHP2 phosphorylation and triggered TLR4 activation respectively through enhanced nuclear translocation of p-65. Moreover, a reciprocal interplay between Neu1 and siglec-E differentially regulates MyD88- and TRIF-pathways through sialic acids on TLR4 as their common substrate during infection. Correspondingly, Neu1 overexpression enhanced MyD88-signalling while still suppressing TRIF-activation. However, silencing siglec-E specifically activated TRIF-signalling. Pro-inflammatory cytokines corresponding to MyD88 and TRIF pathways were also upregulated respectively. Additionally, Neu1 overexpression or siglec-E silencing prevented TLR4 ubiquitination and subsequent degradation by Triad3A. Neu1-overexpression and siglec-E-silencing together followed by infection activated both MyD88 and TRIF-signalling through their enhanced TLR4-association. This elevated the MyD88-specific cytokines and TRIF-mediated IRF3 and IFN-β genes, thus upregulating the pro-inflammatory cytokines and nitric oxide levels and reduced anti-inflammatory cytokines. All these significantly inhibited parasite survival in macrophages thus demonstrating a previously unidentified dualistic regulation of TLR4signaling pathways activation through sialic acids by interplay of Neu1 and siglec-E during Leishmania infection.